REPORT OF COMMITTEE ON ACCOUNTING INSTRUCTION IN ELECTRONIC DATA PROCESSING. - Carlson, Arthur E.; Black, Fred; Brown, Donald W.; Daniels, Howard M.; Schlosser, Robert E.; Gregory, Robert H. (The Accounting Review, 1959)
Data processing can be defined as treating or preparing data by some particular method to obtain desired facts and to produce reports. Business data processing is much broader than computing alone and the requisite equipment for it involves the people, procedures, and communication network to cover the gamut from data origination to report utilization. Accounting instruction in data processing should deal with existing problems rather than futuristic problems and rely upon an evolutionary approach. The instructional objectives of a course in business data processing are to define and delineate the area; to show what is possible; to give an awareness of the problems involved; to describe the experience of others in systems analysis, design and installation and to develop skills in computer programming including the use of programs prepared by others, if well understood. The committee recommends that accounting departments introduce courses dealing with business data processing and new equipment developments.